A Survey of Health Care Professionals' Knowledge and Experience of Foetal Alcohol Spectrum Disorder and Alcohol Use in Pregnancy. (March 2019) - Howlett, Helen; Mackenzie, Shonag; Strehle, Eugen-Matthias; Rankin, Judith; Gray, William K
Background: Foetal alcohol spectrum disorders (FASDs) are one of the most common preventable forms of developmental disability and congenital abnormalities globally, particularly in countries where alcohol is considered socially acceptable. Screening for alcohol use early in pregnancy can facilitate the detection of alcohol-exposed pregnancies and identify women who require further assessment. However, only a small percentage of children with FASD are identified in the United Kingdom. This may be partly attributed to a lack of awareness of the condition by National Health Service (NHS) health professionals. Methods: We developed an online survey to determine health care professionals' (midwives, health visitors, obstetricians, paediatricians, and general practitioners) perceived knowledge, attitudes, and clinical practices relating to alcohol in pregnancy and FASD. Results: There were a total of 250 responses to the surveys (78 midwives, 60 health visitors, 55 obstetricians, 31 paediatricians, and 26 general practitioners). About 58.1% of paediatricians had diagnosed a patient with foetal alcohol syndrome (FAS) or FASD and 36.7% worried about stigmatisation with diagnosis. Paediatricians reported the highest levels of FASD training (54.8%), with much lower levels in midwives (21.3%). This was reflected in perceived knowledge levels; overall, only 19.8% of respondents knew the estimated UK prevalence of FASD for example. Conclusions: We identified a need for training in alcohol screening in pregnancy and FASD to improve awareness and recognition by UK professionals. This could improve patient care from the antenatal period and throughout childhood.